2004
DOI: 10.1111/j.0019-2805.2004.01837.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of streptococcal inhibitor of complement (SIC) and its proteolytic fragments with the human beta defensins

Abstract: SUMMARYStreptococcal inhibitor of complement (SIC) is a 31 kDa extracellular protein produced by a few highly virulent strains of Streptococcus pyogenes (in particular the M1 strain). It has been shown additionally to inhibit four further components of the mucosal innate responseÐ lysozyme, secretory leucocyte proteinase inhibitor, human a-defensin 1 and the cathelicidin LL-37 which are all bactericidal against Group A Streptococci (GAS). We now show that SIC also inhibits variably the antibacterial action of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 18 publications
5
58
1
Order By: Relevance
“…However, when the reciprocal experiment was performed, with LL-37 as the bound substrate, no interaction was observed. A similar result was reported by Fernie-King et al (12) for interactions between SIC and h␤D-2. They suggested that the difference between the two configurations of the assay was attributable to the masking of binding sites when a small molecule (i.e., h␤D-2; 64 amino acids) was bound to a plate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, when the reciprocal experiment was performed, with LL-37 as the bound substrate, no interaction was observed. A similar result was reported by Fernie-King et al (12) for interactions between SIC and h␤D-2. They suggested that the difference between the two configurations of the assay was attributable to the masking of binding sites when a small molecule (i.e., h␤D-2; 64 amino acids) was bound to a plate.…”
Section: Discussionsupporting
confidence: 90%
“…SIC is found in only two S. pyogenes emm types, emm1 and emm57, and was first reported as a ligand for the complement proteins C6 and C7, inhibiting the formation of the membrane attack complex, thereby blocking complement-mediated lysis (10,11). SIC was subsequently shown to inhibit the antimicrobial activity of numerous AMPs and proteins, including LL-37, lysozyme, secretory leukocyte proteinase inhibitor (SLPI), and human ␣ and ␤ defensins (12,13). Additionally, SIC is inhibitory to the antimicrobial activity of several chemokines which are secreted on the pharyngeal epithelial surface (14).…”
mentioning
confidence: 99%
“…The role of Sic and SpeB in the growth of GAS in human saliva. GAS elaborates at least two extracellular proteins, SpeB and Sic, that have been shown to inhibit or inactivate the purified forms of antimicrobial peptides present in saliva (13,14,16,47). Sic is produced mainly by serotype M1 strains, whereas virtually all strains have the speB gene, although protein expression levels are variable (16,27,52).…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation at 1700 × g for 10 min, 1.0 ml of the supernatant was withdrawn and mixed with 1.0 ml of NaOH 0.5 M, and absorbance at 440 nm was measured. Bactericidal Activity --The bactericidal activity toward E. faecalis was assayed using the method of Fernie-King et al 21) The bacterial cells were harvested at the mid-log phase and suspended in 10 mM of Tris-HCl buffer supplemented with 52-fold diluted MRS broth (buffer C, pH 7.5) at the cell density of 2 × 10 5 CFU/ml. An aliquot of the bacterial cell suspension (15 µl) was mixed with an equal volume of HNP-3 (0-2.0 µM) or HD-5 (0-0.25 µM), and the mixture was incubated at 37 • C for 2 hr.…”
Section: Bacterialmentioning
confidence: 99%